From Passive to Radical Revolution in Venezuela's Populist Project. (November 2014) - Brading, Ryan
In December 2001, Hugo Chávez and others changed Venezuela's Bolivarian revolutionary project, which consisted of replacing a corrupt and elitist constitution with a fair and popular one, into a radical one. In its early stages the project corresponded to what Gramsci called a "passive revolution." Attempts by opposition forces to crush the construction of a new populist hegemony (a coup in April 2002 and an indefinite strike in December 2002) were met with popular mobilization that reaffirmed Chávez's hegemonic project. The radical revolution consisted of social programs designed to alleviate the suffering of the poor and consolidated a new hegemonic structure among Venezuela's lower classes. The concept of "radical revolution" provides a theoretical alternative for assessing the extent to which a political project can be described as populist. En diciembre de 2001, Hugo Chávez y otros cambiaron el proyecto revolucionario bolivariano de Venezuela, que consistía en reemplazar una constitución corrupta y elitista por una justa y popular, por uno radical. En sus primeras etapas, el proyecto correspondió a lo que Gramsci definiera como una "revolución pasiva." Intentos por fuerzas de la oposición para frenar la construcción de una nueva hegemonía populista (un golpe de estado en abril de 2002 y una huelga indefinida en diciembre de 2002) se encontraron con una movilización popular que reafirmó el proyecto hegemónico de Chávez. La revolución radical consistió en programas sociales concebidos para aliviar el sufrimiento de los pobres y consolidó una nueva estructura hegemónica entre las clases inferiores de Venezuela. El concepto de "revolución radical" proporciona una alternativa teórica para evaluar la medida en que un proyecto político puede ser descrito como populista.